The role of monocytes and macrophages in idiopathic inflammatory myopathies: insights into pathogenesis and potential targets - Izuka, Shinji; Komai, Toshihiko; Tsuchida, Yumi; Tsuchiya, Haruka; Okamura, Tomohisa; Fujio, Keishi (Frontiers in Immunology, 2025)
Idiopathic inflammatory myopathies (IIMs) are heterogeneous autoimmune disorders characterized by muscle inflammation, weakness, and extramuscular manifestations such as interstitial lung disease, skin rash, arthritis, dysphagia, myocarditis and other systemic organ involvement. Although T and B cells have historically been central to the understanding of IIM immunopathology, monocytes and their differentiated progenitor cells, macrophages, are increasingly being recognized as critical mediators of both tissue damage and repair. In subtypes such as dermatomyositis, immune-mediated necrotizing myopathy and antisynthetase syndrome, macrophages infiltrate skeletal muscle and other affected tissues, contributing to inflammation via production of pro-inflammatory cytokines, chemokines, and reactive oxygen species. Dysregulated interferon signaling, mitochondrial stress, and aberrant metabolic states in these cells further perpetuate tissue injury in IIMs. Conversely, certain macrophage subsets can support muscle fiber regeneration and dampen inflammation, underscoring the dual roles these cells can play. Future research into the heterogeneity of monocytes and macrophages, including single-cell transcriptomic and metabolomic approaches, will help clarify disease mechanisms, identify biomarkers of disease activity and prognosis, and guide novel therapeutic strategies targeting these innate immune cells in IIM.